Evaluasi Pemilihan Supplier Kemasan So Klin Terbaik Menggunakan Analytical Hierarchy Process di PT Sayap Mas Utama - Catur Medilasito; Jasan Supratman (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
PT Sayap Mas Utama is a company engaged in the toiletry industry. The products produced include DAIA detergent, So Klin detergent, Economy cream soap, Blue Wings cream soap and Dang Dut cream soap. The packaging used to pack these products is plastic / cellophane roll. In its production, PT Sayap Mas Utama cooperates with several cellophane suppliers, namely Unipack, Bonavista, Toppan, and Iluva. It is required because if only work with one supplier, the production needs for packaging cannot be fulfilled. This is happened due to the productivity level of PT Sayap Mas Utama is indeed quite high. There are some suppliers has differences in the delivery of goods so that this influence to the productivity of the company. By this research, it is expected that the company can find the best supplier by considering several criteria, namely price, quality, service, delivery accuracy, and quantity suitability. After conducting research using the Analytical Hierarchy Process (AHP) method with the help of the Expert choice application, it was found that Unipack is the best supplier with a weight value of 0.311. Next is Toppan with a weight value of 0.276, Bonavista with a weight value of 0.241 and Iluva with a weight value of 0.158.